Neuro-Psycho Linguistic (NPL) Strategies in Relation to Writing Performance of ESL Learners at the Secondary Level - M, Thenmozhi; Amutha, S. (Universitas Jambi, Magister Program of English Education Department, 2026)
Developing an effective writing skill persists a significant challenge for many learners in English as a Second Language (ESL) contexts. The present study examined the influence of Neuro-Psycho-linguistic (NPL) strategies on the writing performance among secondary-level ESL learners in Tiruchirappalli, Tamil Nadu, India. A cross-sectional survey design was adopted in the present study. The data were collected from 182 ESL learners from secondary level by using a structured questionnaire consisting of 25 items in eight domains of NPL: Anchoring, Modeling, Mirroring, Real-Time Processing Activities (RTPA), Priming, Interactive Learning (IL), Dissociation and Swishing. Learners’ mid-term formative writing performance were obtained from school academic records. The results revealed that anchoring, modeling and mirroring strategies were most frequently utilized by learners. Correlation analysis showed a strong positive relationship between writing performance and NPL strategies such as anchoring, modeling and mirroring. Furthermore, multiple linear regression analysis indicated that anchoring, mirroring, modeling and RTPA significantly predicted on writing performance. The results suggested that NPL-based strategies may support learners’ active cognitive engagement and writing development in ESL contexts.